Key nodes affecting patient satisfaction in a cross-regional referral service process: an empirical analysis study in Sichuan - Xinli Zhang; Tianjin Wang; Yu Yu; Shuzhen Zhao (BMC, 2018)
Abstract Background The referral service is a significant component of healthcare reform in China, and the measurement of patient satisfaction with the referral service process will help to improve the quality of referral medical delivery. Furthermore, the referral service in China includes inter-institutional collaborations between hospitals at different levels and multi-nodes throughout the referral process. It is therefore necessary to identify the key nodes that affect patient satisfaction during the referral service process. Methods This study conducted a questionnaire survey of 110 patients to collect data regarding patient satisfaction at the following healthcare nodes: primary-level hospital, referral appointment registration, claim of appointment number in the outpatient department, examination service, admission service, and overall satisfaction during the referral service process. Correlation analysis and logistic regression methods were used to establish a mathematical model of patient satisfaction between five nodes and overall satisfaction. Additionally, a peak-end model was formed to identify the peak node impacting overall patient satisfaction during the referral service based on the sample data. Results Over 80% of referral patients rated the overall referral service as 'good'. The correlation analysis revealed that there was a significant correlation between the satisfaction of each node and the overall satisfaction (P < 0.05). The results of the regression model showed that the satisfaction of five nodes determined the overall satisfaction and that "admission service at the higher-level hospital" exerted the greatest impact on overall satisfaction (β = 0.312), while "referral appointment registration" had the lowest influence on overall satisfaction (β = 0.177). The peak-end model also revealed that "admission service at the higher-level hospital" had a greater effect on overall satisfaction. Conclusion Our study showed that the key nodes affecting patient satisfaction were "transferring service at the primary-level hospital" and "admission service at the higher-level hospital". Furthermore, the efficacy of the referral services is determined by the gatekeepers' management of the referral system at the primary-level hospital and the allocation and management of bed resources at the higher-level hospital. These findings can serve as a science-based guidance for them to improve their performance in inter-regional healthcare collaborations in the referral service process.